Post disaster waste management strategies in developing countries: Case of Sri Lanka - Karunasena, Gayani; Amaratunga, Dilanthi; Haigh, Richard; Lill, Irene (International Journal of Strategic Property Management, 2009)
Disasters cause substantial damage around the world. This causes serious environmental and economic burden on normal living conditions, reconstruction and general waste collection processes. Within this context, waste management has emerged as a critical issue in responding to a disaster. Thus, this paper addresses post disaster waste management strategies adopted in developing countries and applicability of best global practices in respect of challenges encountered. Comprehensive literature review and field survey among national level institutes in Sri Lanka were conducted to gather information and semi‐structured interviews were used as a method of data collection. The findings revealed that strategies, issues and challenges are varying according to type of disaster, magnitude, location, country etc. Further, poor implementation of prevailing rules and regulations; poor standards of local expertise and capacities, inadequate funds, lack of communication and coordination are identified as key issues encountered. First Publish Online: 18 Oct 2010